Correlation between the structure and wettability of photoswitchable hydrophilic azobenzene monolayers on silicon - Pei, Xiaowei; Fernandes, Antony; Mathy, Bertrand; Laloyaux, Xavier; Nysten, Bernard; Riant, Olivier; Jonas, Alain M (Langmuir, 2011)
Photoresponsive monolayers of hydrophilically substituted azobenzenes have been prepared by reaction on aminosilane monolayers on silicon surfaces. Grafting densities in the 0.2-1.0 molecule/nm(2) range were determined by X-ray reflectometry. The monolayers exhibit reversible photoisomerization, switching from a more hydrophilic trans state to a less hydrophilic cis state upon UV irradiation, in contrast with the usual behavior of most azobenzene monolayers that switch from a less to a more hydrophilic state. This indicates that the wettability is not dominated by the change in the dipole moment of the azobenzene moiety but originates from variations in the composition of the outer surface of the monolayers resulting from the reorientation of the substituent groups. The light-driven change in the water contact angle correlates linearly with the grafting density but remains small. However, the wettability contrast can be increased by forcing the molecules to stand in an improved vertical orientation, either by densifying the underlying aminosilane monolayer or by filling the voids left at the bottom of the layer of grafted azobenzene molecules.